Disseminated tinea incognita in a patient with ichthyosis vulgaris and eczema. (26th August 2020) - Steele, L.; Hong, A.; Balogh, P.; O'Toole, E. A.; Harwood, C. A.; Maruthappu, T.
Abstract : Click here for the corresponding questions to this CME article.